2022
DOI: 10.1186/s12886-022-02544-2
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival sac bacterial culture of patients using levofloxacin eye drops before cataract surgery: a real-world, retrospective study

Abstract: Background The use of antibiotics preoperatively is effective to decrease the incidence of ocular bacterial infections but may lead to high resistance rate, especially on patients with multi-risk clinical factors. This study systematically analyzed real-world data (RWD) of patients to reveal the association between clinical factors and conjunctival sac bacterial load and offer prophylaxis suggestions. Methods We retrieved RWD of patients using levo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…Our study also demonstrated that certain clinical factors, such as being female, having meibomian gland dysfunction (MGD), diabetes, and recent history of infections, were associated with a higher bacterial load in the conjunctival sac. This has been con rmed in previous studies as well [2,3,24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study also demonstrated that certain clinical factors, such as being female, having meibomian gland dysfunction (MGD), diabetes, and recent history of infections, were associated with a higher bacterial load in the conjunctival sac. This has been con rmed in previous studies as well [2,3,24].…”
Section: Discussionsupporting
confidence: 88%
“…This nding aligns with our results. Wang et al found that after three days of preoperative use of levo oxacin eye drops, Staphylococcus epidermidis, Kocuria rosea, and Micrococcus luteus were the top three strains with the highest positive culture rates [24]. This suggests that preoperative use of antibiotics does not completely eliminate the presence of the Micrococcus in the conjunctival sac, which may result in opportunistic eye infections after surgery.…”
Section: Discussionmentioning
confidence: 99%